Bat diversity (Mammalia: Chiroptera) in the Parcani limestone mines - Larion, Alina; Nistreanu, Victoria; Caldari, Vladislav; Dibolscaia, Natalia; Sîtnic, Victor (Acta et Commentationes Exact and Natural Sciences, 2025)
The study was conducted in 2023 – 2024 in various seasons in the limestone mine near Parcani locality. 7 species of bats were recorded: Rhinolophus hipposideros, Myotis blythii, Myotis daubentonii, Myotis dasycneme, Myotis mystacinus, Plecotus auritus and Plecotus austriacus. The structure of bat community was different depending on the season. The highest number of individuals was registered during the hibernation period, when M. blythii was the most abundant species. All species recorded in Parcani mine are protected at national and European level. The Parcani mine is an important hibernation and summer roost for many rare bat species.